Regulating Labour Relations in China : The Challenge of Adapting to the Socialist Market Economy - Potter, Pitman; Jianyong, Li (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1996)
This paper examines the new Labour Law of the PRC, effective January 1, 1995, in the light of current and historical conditions of labour relations in China. Provisions regarding the labour contract system and dispute resolution are discussed in greater detail. Issues related to the introduction of collective bargaining and to the relationship between trade unions and the Communist Party are also examined. In their overall assessment, the authors recognize the potential significance of the Labour Law as a major step towards the legal protection of workers' rights, but point out that its effectiveness could be undermined by the preeminent policy of economic growth, by concerns about political control, and by obstacles to full implementation.